Toll-like receptor-4 is a target for suppression of proliferation and chemoresistance in HepG2 hepatoblastoma cells. Issue 1 (1st November 2015) - Hsiao, Chih-Cheng; Chen, Po-Han; Cheng, Cheng-I.; Tsai, Ming-Shian; Chang, Chih-Yang; Lu, Shang-Chieh; Hsieh, Ming-Chu; Lin, Yu-Chun; Lee, Po-Huang; Kao, Ying-Hsien
Highlights: LPS differentially upregulates TLR4 in HepG2 but not HCC cells. TLR4 activation increases NO production and proliferation in HepG2 cells. PI3K and MAPK pathways are involved in NO production and proliferation of HepG2 cells. TLR4 gene modifications affect proliferation and chemoresistance of HepG2 cells. TLR4 may serve as an oncotarget for Hepatoblastoma. Abstract: Toll-like receptor-4 (TLR4) is known to influence growth and migration of hepatocellular tumors; however, its role in hepatoblastoma remains poorly understood. This study investigated the regulatory role of TLR4 in proliferation and chemoresistance of HepG2 hepatoblastoma cells. Treatment with lipopolysaccharide (LPS), a TLR4 agonist, was found to significantly upregulate TLR4 expression in HepG2 cells, but not in malignant Huh-7 and Sk-Hep1 hepatocellular carcinoma cells. Additionally, IL-6 enhanced LPS-induced TLR4 upregulation. LPS-stimulated TLR4 activation increased proliferation, nitric oxide synthase (NOS) expression, and NO production in HepG2 cells. Chemotherapeutic agents, cisplatin and doxorubicin, effectively inhibited TLR4 expression in HepG2 cells. Characterization of LPS-induced signaling activation and blockade with kinase inhibitors revealed the involvement of Akt and MAPK pathways in LPS-enhanced NO release from, and proliferation of HepG2 cells. Mechanistically, gene modifications as a result of TLR4 transfection and siRNA-mediated knockdown further demonstrated a crucial role for TLR4 in the regulation of NOS expression, cell proliferation, and chemoresistance in HepG2 cells. These findings suggest that targeting TLR4 expression and its cognate signaling may modulate proliferation and chemosensitivity in hepatoblastoma cells and serve as a potential therapeutic target.